Silent Protesters or Acceptors? The Reaction of the Russian-speakers to the Removal of the Soviet Monuments in Latvia and Estonia after Russia’s Full-scale Invasion of Ukraine* - Kuczyńska-Zonik, Aleksandra (Politologija, 2024)
For a long time the approach of the both two Baltic states to the Soviet heritage was formed by: (1) international and bilateral agreements which obliged states to protect monuments and memorial sites of the Soviet Army as well as (2) numerous Russian-speaking community for whom the Soviet statues constitute its cultural identity. The situation has significantly changed due to Russia’s aggressive policy against Ukraine, when the authorities made several attempts to remove the Soviet monuments. This brought some controversies and objections among the Russian-speaking communities in Latvia and Estonia. The paper focuses on the transformation of the national historical narrative toward the Soviet monuments and the processes of the adapting of the Russian-speaking community to the official memory discourse. More specifically, the aim is to explore the ways in which the Russian-speaking residents reacted to the removal of the Soviet monuments. The concept of resistance was applied in order to explore and synthesize the outcomes of the interviews carried out among Russian-speaking communities in Latvia and Estonia. It is argued here that the reconstruction of the public space by shifting the most visual symbol of the victory of the Red Army in the WWII has not induced hot feelings among the Russian-speaking society, and thus, it has not motivated community to take part in the open protest against the removal. Most of the minority representatives stayed passive and silent adapting to the new reality.
Keywords: resistance; national minority; Soviet monuments; Latvia; Estonia